Household socioeconomic factors and minimum dietary diversity among infants and young children in Kebumen District of Indonesia - Tantri Nofitasari; Nur Indah Rahmawati; Eka Nurhayati; Fatimah Fatimah; Tri Siswati; Bunga Astria Paramashanti (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2023)
Background: Despite its benefits on child health and nutrition, the proportion of Indonesian children meeting the minimum dietary diversity remains suboptimal.Objective: This study aimed to examine the association between household socioeconomic factors and minimum dietary diversity among young children 6-23 months.Methods: A cross-sectional study was conducted in Kebumen District of Indonesia. We selected a total of 356 children using multistage cluster sampling. The main outcome was minimum dietary diversity. Explanatory variables were household socioeconomic factors, including parental education, parental occupation, and household income.Results: The percentage of children meeting minimum dietary diversity was 43.5%. The multiple logistic regression results showed that high household income was significantly associated with minimum dietary diversity (AOR= 2.27; 95%CI: 1.38-3.72). Other socioeconomic factors, such as parental education and occupation, were unrelated to minimum dietary diversity among infants and young children.Conclusion: Minimum dietary diversity is low in Kebumen District. Wealthier households are more likely to feed their children with a diversified diet than poorer households. A combination of nutrition-specific and nutrition-sensitive interventions is needed to achieve appropriate infant and young child feeding practices.